2016
DOI: 10.20517/2347-8659.2016.25
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of microparticles in neuroimmune signaling of microglial cells

Abstract: Aim: Submicron fragments termed microparticles (MPs), derived from all major central nervous system cell types including neurons and glia (microglia, astrocytes, oligodendrocytes), have emerged as novel intercellular signaling agents. This study tested the hypothesis that MPs derived from activated microglia, which represent the mononuclear phagocyte system in the brain, could induce pro-inflammatory and cytotoxic responses of microglia in an autocrine or paracrine manner. Methods: Human THP-1 monocytic cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Moreover, the MPs released by THP-1 cells in response to TFAM were able to activate THP-1 cells in an autocrine manner and led to cytotoxicity as shown by a decrease in SH-SY5Y neuronal cell viability following exposure to supernatant from MP-stimulated monocytic cells. The MPs derived from TFAM-stimulated THP-1 cells also induced the secretion of MCP-1 by THP-1 cells [83]. These results indicate that TFAM may act as a DAMP that can activate microglial cells to release MPs that possess neurotoxic and inflammatory properties and could contribute to neurodegenerative disease pathology.…”
Section: Mitochondrial Transcription Factor a (Tfam)mentioning
confidence: 99%
“…Moreover, the MPs released by THP-1 cells in response to TFAM were able to activate THP-1 cells in an autocrine manner and led to cytotoxicity as shown by a decrease in SH-SY5Y neuronal cell viability following exposure to supernatant from MP-stimulated monocytic cells. The MPs derived from TFAM-stimulated THP-1 cells also induced the secretion of MCP-1 by THP-1 cells [83]. These results indicate that TFAM may act as a DAMP that can activate microglial cells to release MPs that possess neurotoxic and inflammatory properties and could contribute to neurodegenerative disease pathology.…”
Section: Mitochondrial Transcription Factor a (Tfam)mentioning
confidence: 99%
“…Moreover, Schindler et al. [140] also showed in their study that TFAM can stimulate THP‐1 cells to release microparticles (MP), which act as proinflammatory stimulants, leading to MCP‐1 secretion. eATP also activates the P2Y receptors causing an outward potassium movement, leading to a PI‐3K‐dependent chemotaxis of microglia [141].…”
Section: Mitochondrial Damps In Diseasementioning
confidence: 99%
“…Activated microglia release MPs carrying IL-1β, and these microgliaderived MPs enhanced inflammatory response by transferring inflammatory stimuli to other microglia (197)(198)(199). A study by Schindler et al (200) using cultured human mononuclear phagocytes demonstrated that microglia-derived MPs induced NF-κB activation, leading to the release of proinflammatory cytokines (200). The role of microglia-derived MPs was further substantiated in a study investigating neuroinflammation following brain traumatic injury whereby the MPs (identified through P2Y12/CD45 + ) derived from neuroinflammation that developed in the brain were released into the circulation and initiated neuroinflammation in naive control animals (201).…”
Section: Mps and Inflammationmentioning
confidence: 99%